Proximal chain strength and coordination concepts to maximize injury protection and transfer of training effects for competitive baseball players - Crotin, R. L.; Iniguez, X.; Carlson, E. M. (Strength and Conditioning Journal, 2023)
Proximal injuries involving the core, intercostal musculature, and spine are the third leading cause of playing time loss in professional baseball. Long seasons and rotational unilaterality from hitting, throwing, and pitching exposes athletes to overuse risks, including disc herniation, spondyloses, spondylosis, facet joint syndromes, and pars lumbar fractures. This article describes injury epidemiology, rotational biomechanics including energy transfer dynamics, and offers injury prevention insights with minimal equipment. Ultimately, the goal of this article is to provide concepts to improve strength and coordination in training to offer greater injury protection and performance in baseball.